Schistosoma mansoni Infection: A Major Contributor of Reduced Effective T Helper Responses against Plasmodium falciparum and Schistosoma mansoni Co-Infection in ex vivo: A Cross-Sectional Study to Assess Th1, Th2 & Th17 Immune Responses - Candia, Rowel; Nabatanzi, Rose; Olobo, Joseph; Auma, Ann; Asiimwe, Benon; Mbabazi, Olive; Bayiyana, Alice; Enzaru, Annet; Tukahebwa, Edridah (Open Journal of Immunology, 2017)
Parasitic worms evade immune responses, and interactions between diseases can cause altered immunologic outcomes compared to what usually occurs with single infections. These interactions may influence vaccine and chemotherapeutic efficacy. Schistosoma mansoni and Plasmodium falciparum are co-endemic in Uganda and are the leading parasitic causes of public health problems across sub-Saharan Africa. Objectives: The overall aim was therefore, to elucidate the impact of S. mansoni infection on protective T helper immune responses on P. falciparum and S. mansoni co-infection. Methodology: This study evaluated the T helper immune responses in individuals with independent S. mansoni infection, independent P. falciparum infection, co-infection and non-infection in school attending children in a co-endemic area along Lake Victoria shores, Uganda. Immune responses were categorized into Th1, Th2, and Th17 based on unique cytokine(s) produced by the T helper subpopulation in ex vivo. Kato Katz thick smears and circulating cathodic antigen tests were performed for S. mansoni screening, whereas thick and thin blood smear techniques were performed for P. falciparum screening. Results: We observed an up regulated Th1 T helper subpopulation in independent P. falciparum infections compared to the uninfected group. Suboptimal T helper immune responses were detected in independent S. mansoni infections characterized by significantly down regulated Th1 (Z = -1.425, p = 0.0313) response in comparison to the non-infected group. Suboptimal T helper immune responses were also recorded in the co-infected individuals characterized by significantly down regulated Th1 (Z = -3.260, p = 0.0273) and Th2 (Z = -1.180, p = 0.0078) responses compared to independent P. falciparum. Conclusions: S. mansoni infection is a major contributor of a reduced effective T helper immune response against P. falciparum in P. falciparum and S. mansoni co-infection.